Participation of women members of the parliament in peacebuilding efforts: The case of Bangsamoro government - Indigay, Abdulhalem N.; Salazar, Al Bismarck S.; Kayama, Kamlon M.; Maulana, Saima S. (Edelweiss Applied Science and Technology, 2024)
This study explores the participation of Bangsamoro women Members of Parliament (MPs) in governance and peacebuilding efforts within the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). It examines the effectiveness of their involvement in peacebuilding, the challenges they encounter, and their recommendations for improving their political participation. The findings reveal that despite a male-dominated political landscape, women MPs actively contribute to policymaking, legislation, and advocating for gender equality. Their participation has positively impacted peacebuilding efforts by pushing for policies that protect women's rights and promote inclusive governance. However, women MPs face significant barriers, including societal norms, cultural practices, and institutional biases that marginalize their voices. Strategies such as community consultations, legal and religious advocacy, empowerment through training, and mentorship have been employed to overcome these challenges. The study concludes with recommendations for enhancing women’s political participation, including continued education, stronger relationships with constituents, and promoting moral governance. These efforts are crucial for advancing gender equality and fostering a more inclusive and effective political environment in the BARMM.